2012
DOI: 10.1103/physrevlett.109.125003
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Mode Conversion Associated with Kinetic Alfvén Waves

Abstract: We report the first three-dimensional (3D) ion particle simulation of mode conversion from a fast mode compressional wave to kinetic Alfvén waves (KAWs) that occurs when a compressional mode propagates across a plasma boundary into a region of increasing Alfvén velocity. The magnetic field is oriented in the z direction perpendicular to the gradients in the background density and magnetic field (x direction). Following a stage dominated by linear physics in which KAWs with large wave numbers k(x)ρ(i)∼1 (with ρ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 35 publications
8
66
0
Order By: Relevance
“…(20) indicates that the KAW decay process maximizes around θ ±π/2; i.e., k 0⊥ ⊥ k −⊥ , and |k ⊥ ρ i | ∼ O(1). Both predictions have recently been observed in numerical simulations [42].…”
Section: Nonlinear Wave-wave Interactionssupporting
confidence: 67%
“…(20) indicates that the KAW decay process maximizes around θ ±π/2; i.e., k 0⊥ ⊥ k −⊥ , and |k ⊥ ρ i | ∼ O(1). Both predictions have recently been observed in numerical simulations [42].…”
Section: Nonlinear Wave-wave Interactionssupporting
confidence: 67%
“…Both predictions have recently been observed in numerical simulations. 30 Equations (21) and (25) indicate that the decay instabilities are quantitatively and qualitatively different in the MHD and kinetic regimes. Specifically, we note that…”
Section: Finite Ion Compressibility and Parametric Decaysmentioning
confidence: 99%
“…46 Furthermore, the 2-D global hybrid model was used by Hong, Swift, and Lin 47 to study the ion dynamics associated with Alfven waves in the near-Earth magnetotail. Recently, Lin, Johnson, and Wang 21,22 investigated the mode conversion and structure of KAWs around the magnetopause boundary layer with both 2-D and 3-D hybrid simulations. Meanwhile, the generation of KAWs in the global magnetotail has not been addressed, although a 2-D hybrid simulation has already been utilized to investigate the generation of KAWs in a non-uniform magnetospheric plasma boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that KAWs can be generated through mode conversion, 1,5,[20][21][22] phase mixing, 6,23,24 resonant absorption, 11,25 velocity shear, 26,27 etc. Hasegawa 1 proposed that MHD surface waves could couple to KAWs via an interaction with the density gradient at the plasma sheet-tail lobe boundary.…”
Section: Introductionmentioning
confidence: 99%